Management of Mental Health in Nigerian Tertiary Institutions - Chinwuba, Mary Adanna; Salman, Adamu Awwal (Journal of Innovation in Education and Social Research, 2026)
The study explored various strategies to promote mental health in Nigerian tertiary institutions. The study used secondary data. The secondary data were collected from both print and online publication. The study concluded that promoting mental health in tertiary institutions requires a multi-dimensional approach involving accessible campus counseling services, mental health awareness campaigns, integration of mental health education into the curriculum, peer support systems, stress management workshops, supportive campus environments, and strategic collaborations with external mental health organizations. Based on these findings, the study recommends that establishment and strengthening of campus mental health services: conduct regular mental health awareness campaigns: integrate mental health education into the curriculum: develop peer support networks: organize stress management and life skills workshops: create a supportive and inclusive campus environment: collaborate with external mental health agencies: monitor and evaluate mental health programs and government and policy support.